Ethnicity as a "regularity in dispersion": Discourses on comedy and identity among Chinese Indonesian youth - Nugroho, Stefani (SIMULACRA: JURNAL SOSIOLOGI, 2024)
This article examines how young Chinese Indonesians interpret and engage with representations in comedy performed by Chinese Indonesian comedians. Using a poststructuralist framework, the article argues that ethnic identity is contingent, shaped by shared relational experiences with the majority, rather than by fixed essential traits, reflecting what Laclau and Mouffe have termed a "regularity in dispersion". Data was collected through a focus group discussion with twelve participants, where they were presented with a preselected set of six video clips containing comedic performances. Two intertwining themes based on the participants' responses to the videos were developed using reflexive thematic analysis: 1) diverging perspectives from the comedians' reductive, stereotypical and homogenizing representations of Chinese Indonesians and 2) converging perspectives on the jokes centered on boundary-maintaining social dynamics between the majority and themselves, such as discrimination and practices of endogamy. These themes present the contingent nature of ethnic identity as primarily shaped by relational social factors instead of determined by inherent traits. This research brings to the forefront the importance of examining the contextual and relational construction of ethnicity.